Dinamika Akses Informasi Wisatawan antar Generasi pada Obyek Wisata Minat Khusus di Kabupaten Bantul - Fian Damasdino (Media Wisata, 2017)
Every generation of human has unique experience use information and communication technology. Each generation has different characteristics, such as knowledge, experience and expertise in interacting with the media access to information not only electronic media but also print media and online media. This research is a kind of quantitative research with a survey research method. The research location in 10 tourism destination in Bantul: Banyunibo Waterfall in Pajangan, Mangunan, Pine Forest, Siluk Suspension Bridge in Imogiri, Geospatial Coastal Dune Sand in Parangtritis, Becici Hill in Dlingo, Pulosari Waterfall in Pajangan, Watu Lumbung in Parangtritis, Tri Panjung Hill in Dlingo, Lepo Lake in Dlingo, and Mangunan Hill in Dlingo. Sampling using non-probbably sampling technique because the population in this research is not known for certain. This is due to the absence of data collection of visitor tourist by the local government. Sampling was conducted during May-September 2016 at 10 tourism destination. The collection of data taken with questionnaires, observation, and documentation library. Once the data is collected and processed by quantitative analysis using statistical tools, frequency distributions and cross tables (crosstabs)